Correction of destructive changes in connective tissues of different organs during chronic nitrate and fluoride intoxication by nanosized silica oxide - Akimov, O. Ye.; Kovalova, I. O.; Kostenko, V. O. (Journal of Education, Health and Sport, 2019)
This experiment carried on 35 white Wistar rats aimed at studying the markers of connective tissue destruction during chronic nitrate-fluoride intoxication and its correction by nanosized silica oxide. It has been found out that co-administration of sodium fluoride (10 mg/kg body weight) and sodium nitrate (500 mg/kg of body weight) for 30 days increases the total content of glycosaminoglycans (GAG), heparin/heparan and keratan/dermatan fractions, as well as content of chondroitin fraction and concentration of L-oxyproline in the gastric mucosa. The content of N-acetylneuraminic acid (NANA), free L-oxyproline and gexuronic acids are increased in femoral bone and lumbar vertebrae. These changes point to depolymerization of componets of organic connective tissues matrix (collagen, glycoproteins, proteoglycans). Application of nanosized silica oxide suspension under conditions of chronic nitrate-fluoride intoxication reduces the total GAG content, keratan / dermatane fraction ratio, chondroitin fraction and L-oxyproline concentration in the gastric mucosa. We also observed a decrease in free L-oxyproline concentration, gexuronic acids and NANA content in femoral bone and vertebrae. The results allowed us to conclude that chronic nitrate-fluoride intoxication leads to the destruction of connective tissue components in different organs (gastric mucous membrane, femoral bones and vertebrae). Usage of nanosized silica oxide under conditions of chronic nitrate-fluoride intoxication reduces the destruction of connective tissue in these structures.